English Teacher’s Questions in Classroom Activity at SMPN11 Tidore Kepulauan - Vebiyanti Nasir (Peneliti.net, 2023)
This study aims to determine the types of questions in English lesson given by the English teacher in the classroom activity and the function of the questions given. This study was conducted on teachers of first grade at SMPN 11 Tidore Kepulauan. This study was descriptive qualitative and the technique of data collection is by observing and interviewing. The results of this study were that in the grade 1, teacher at SMPN 11 Tidore Kepulauan only used 2 types of questions, namely Display Questions and Referential Questions, there were no Open - Closed Questions in the learning process because the teacher considers the class level of the students is still low. The purpose of the teacher in giving Display Questions and Referential Questions type questions was to find out students' knowledge of what they are learning and to provide opportunities for students to dare to ask questions and speak English in the classroom